2018
DOI: 10.1029/2018tc005010
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic Rotation History of Borneo and Sundaland, SE Asia Revealed by Paleomagnetism, Seismic Tomography, and Kinematic Reconstruction

Abstract: SE Asia comprises a heterogeneous assemblage of fragments derived from Cathaysia (Eurasia) in the north and Gondwana in the south, separated by suture zones representing closed former ocean basins. The western part of the region comprises Sundaland, which was formed by Late Permian‐Triassic amalgamation of continental and arc fragments now found in Indochina, the Thai Penisula, Peninsular Malaysia, and Sumatra. On Borneo, the Kuching Zone formed the eastern margin of Sundaland since the Triassic. To the SE of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 119 publications
1
46
0
Order By: Relevance
“…From this template, we modified the tectonic history of the BT to reflect our paleomagnetic results. Furthermore, the positions and paleogeography of Greater India, Indochina, Kohistan, Lhasa, Sumatra and Woyla were configured to better reflect more recent studies 8,67,68 . In Figure 1b, the global reconstruction with the Greater India basin hypothesis is based on a different set of poles of rotations 5 .…”
Section: Plate Modelmentioning
confidence: 99%
“…From this template, we modified the tectonic history of the BT to reflect our paleomagnetic results. Furthermore, the positions and paleogeography of Greater India, Indochina, Kohistan, Lhasa, Sumatra and Woyla were configured to better reflect more recent studies 8,67,68 . In Figure 1b, the global reconstruction with the Greater India basin hypothesis is based on a different set of poles of rotations 5 .…”
Section: Plate Modelmentioning
confidence: 99%
“…The extrusion model generally assumes that the Palawan Continental Terrane and Borneo were attached to Indochina as a single block that was extruded to the southeast with clockwise rotation due to the India‐Eurasia collision (Figure a; Briais et al, ; Leloup et al, ; Tapponnier et al, ). However, most of the geological observations do not support this model: (a) The direction and magnitude of strike‐slip displacement along the line of the Red River Fault Zone‐East Vietnam Boundary Fault are not consistent and fail to explain such large‐scale lithospheric extension and oceanic spreading in the western South China Sea region (Clift et al, ; Fyhn et al, ; Morley, ); (b) the newly acquired palaeomagnetic data from Borneo suggested a counterclockwise rotation during the Cenozoic, although the timing and magnitude of rotation are still debated (Advokaat et al, ; Fuller et al, ; Schmidtke, Fuller, & Haston, ); (c) while the collision between India and Eurasia occurred as early as in the Early Cenozoic, it was not until the Oligocene that the significant sinistral motion along the Red River Fault Zone‐East Vietnam Boundary Fault initiated, clearly too late to explain the widespread rifting extension of the region during the Late Palaeocene–Eocene.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that proto-South China Sea subduction and South China Sea seafloor spreading were significant regional tectonic events (e.g., Hall, 2002;Cullen, 2010;Zahirovic et al, 2014;Wu and Suppe, 2018). Borneo rotated up to ~45° counterclockwise after the late Eocene (Advokaat et al, 2018). From the early Cenozoic to the mid-Miocene, NW Borneo was apparently an active margin due to southward proto-South China Sea subduction under Borneo ( Fig.…”
Section: ■ Regional Geologic Setting Tectonostratigraphymentioning
confidence: 98%
“…Three-dimensional (3-D) seismic survey location is shown by the bold black box. Deep-water fold belt anticlines were interpreted from time structure maps in Grant (2004) and Gee et al (2007) reconstructions of NW Borneo and the surrounding region are highly debated (e.g., Hall, 2002;Cullen, 2010;Zahirovic et al, 2014;Advokaat et al, 2018;Wu and Suppe, 2018). It is generally agreed that proto-South China Sea subduction and South China Sea seafloor spreading were significant regional tectonic events (e.g., Hall, 2002;Cullen, 2010;Zahirovic et al, 2014;Wu and Suppe, 2018).…”
Section: ■ Regional Geologic Setting Tectonostratigraphymentioning
confidence: 99%